"You're still an angry man": Parole boards and logics of criminalized masculinity. (November 2021) - Greene, Joss; Dalke, Isaac
Scholars have theorized "criminalized masculinity" as performances of criminalized men. We refigure the concept to identify narratives that facilitate and legitimize control of criminalized populations. Drawing on 109 California parole hearings, we show how parole commissioners use logics of deserving and dangerous masculinity to assert a boundary between men deemed ready for social reintegration and men relegated to captivity. Commissioners articulate criminalized masculinity along three dimensions: relationship to self; relationship to male peers; and relationship to subordinate others like women and children. These gender logics are materially significant because they justify parole grants and denials. Symbolically, narratives of masculinity legitimize the prison's work of racialized social exclusion and obscure structural dynamics of punishment under accounts of individual difference.